PENGARUH KEPEMIMPINAN, KEJELASAN SASARAN ANGGARAN, DAN PENGAWASAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN BEBANDEM KABUPATEN KARANGASEM - Ni Nyoman Pebi Krisnanti; Kadek Dewi Padnyawati; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2022)
The study aims to investigate the effectiveness of leadership, clarity of budget targets, supervision on the accountability of village fund management. Village office employees from 8 villages in the sub-district of bebandem as the population. Purposive sampling method was used in determining the sample so that 72 respondents were obtained. Following the instrument test and the classical assumption test performed, multiple linear regressions analysis, determination,t test and F test were used to evaluate the data. The study resulted in there indicate that leadership, clarity of budget targets, and supervision take effect a positive and significant for the accountability of village fund management in village governments throughout the bebandem district, karangasem Regency.